Understanding Loan Aversion in Education - Angela Boatman; Brent J. Evans; Adela Soliz (SAGE Publishing, 2017)
Although prior research has suggested that some students may be averse to taking out loans to finance their college education, there is little empirical evidence showing the extent to which loan aversion exists or how it affects different populations of students. This study provides the first large-scale quantitative evidence of levels of loan aversion in the United States. Using survey data collected on more than 6,000 individuals, we examine the frequency of loan aversion in three distinct populations. Depending on the measure, between 20 and 40% of high school seniors exhibit loan aversion with lower rates among community college students and adults not in college. Women are less likely to express loan-averse attitudes than men, and Hispanic respondents are more likely to be loan averse than White respondents.